What Do We Know About Medical Cannabis in Neurological Disorders and What Are the Next Steps? - Lacroix, Clémence; Alleman-Brimault, Isabelle; Zalta, Arnaud; Rouby, Frank; Cassé-Perrot, Catherine; Jouve, Elisabeth; Attolini, Laurence; Guilhaumou, Romain; Micallef, Joëlle; Blin, Olivier (Frontiers in Pharmacology, 2022)
Medical use of cannabis has been receiving growing attention over the last past decades. As we know that endocannabinoid system is largely involved in neurological disorders, we focus on the scientific rationale of medical cannabis in three neurological disorders: amyotrophic lateral sclerosis, Parkinson disease and Alzheimer disease through pharmacological plausibility, clinical studies and the patients’ view. Clinical studies exploring medical cannabis in these disorders show different results depending on the methods and outcomes. Some show benefits on motor symptoms, and others on non-motor symptoms and quality of life. Concerning the patients’ view, several web surveys were managed highlighting a real use of cannabis to relieve symptoms of neurological disorders, mostly outside a medical pathway. This anarchic use keeps questioning particularly in term of risks: consumption of street cannabis, drug-drug interactions with usual medical treatment, consideration of medical history and adverse reactions (psychiatric, respiratory, cardiovascular disorders…) underlining the importance of a medical supervision. To date, most scientific data support therapeutic potential of cannabis in neurological disorders. As far as patients and patients’ associations are calling for it, there is an urgent need to manage clinical studies to provide stronger evidence and secure medical cannabis use.